Plasmonic photothermal therapy: Approaches to advanced strategy. Issue 10 (19th July 2018) - Bucharskaya, Alla B.; Maslyakova, Galina N.; Chekhonatskaya, Marina L.; Terentyuk, Georgy S.; Navolokin, Nikita A.; Khlebtsov, Boris N.; Khlebtsov, Nikolai G.; Bashkatov, Alexey N.; Genina, Elina A.; Tuchin, Valery V.
Abstract : Background: The analysis of recent studies on plasmonic photothermal therapy (PPT) after intravenous administration of gold nanorods (GNRs) has demonstrated that the effectiveness of nanoparticle‐assisted laser hyperthermia depends on a correct dosage strategy of nanoparticle administration. Accumulation of GNRs in tumor tissue dramatically increases the local heating of the tumor without damage to healthy tissues. However, the optimal doses of GNR intravenous injections (IVIs) for effective accumulation in tumors, and optimal protocols of PPT are not designed yet. The current study aims to improve the efficacy of PPT in tumor‐bearing rats using multiple fractional intravenous administration of GNRs. Materials and Methods: For PPT experiments, the GNRs with aspect ratio of 4.1 were functionalized with thiolated polyethylene glycol (PEG) and their suspensions were used for multiple fractional intravenous administration in outbred albino male rats with experimental model of rat liver cancer (cholangiocarcinoma line PC‐1). Doppler ultrasonography was performed to characterize the vascularity of transplanted rat tumors before any treatment. After a final injection of GNRs, tumor was irradiated during 15 minutes by 808‐nm NIR diode laser at a power density 2.3 W/cm 2 . The animals were withdrawn from the experiment and sampling of tissues for morphological study and gold accumulation was performed 24 hours and 3 weeks after PPT. Results: The multiple IVIs of gold nanorods and further PPT of transplanted cholangiocarcinoma provided significant damage to tumor tissue resulting in pronounced necrotic mass and retardation of the tumor growth. More importantly, the proposed PPT protocol had low toxicity as evidenced by histological examination of internal organs. The efficiency of PPT depends on the presence of newly formed vasculature as revealed by the Doppler ultrasound investigation. Conclusion: The repeatable IVIs promote greater of GNR accumulation within the tumor thus resulting in higher PPT efficacy. Accompanying ultrasonography can be useful for prognosis and monitoring of treatment. Lasers Surg. Med. 50:1025–1033, 2018. © 2018 Wiley Periodicals, Inc.